Potensi Buah Jambu Biji Merah (Psidium guajava L.) dalam Meningkatkan Kadar Hemoglobin - Achmad Syaiful Hadi (Universitas Sebelas Maret, 2023)
Essential part of red blood cells is hemoglobin, an iron-containing protein that transports oxygen and carbon dioxide throughout the body and serves as a pigment to give blood its red hue. Low hemoglobin levels and decreased iron storage may be contributing factors to anemia; nevertheless, vitamin C needs to be present in every food taken for the body to properly absorb iron. Consume fruits rich in vitamin C and other nutrients, such red guava (Psidium guajava L.), which is one of these fruits and offers advantages for people with anemia.Red guava (Psidium guajava L.) has 42.9 mg of vitamin C per 100 grams, or 0.429 mg/gram. The purpose of this paper is to promote awareness of the red guava's (Psidium guajava L.) ability to increase hemoglobin levels. Results from literature analyses of various scientific papers show that consumption of red guava juice increases hemoglobin levels in male white rats, pregnant women, and teenage females.